Study Of Contraceptive Use Among Married Women in A Slum in Mumbai - Kiran G Makade; Manasi Padhyegurjar; Shekhar B Padhyegurjar; R N Kulkarni (Medsci Publications, 2012)
Objectives: To study 1) awareness, practices, preferred method of contraception, emergency contraceptive and Medical Termination of Pregnancy (MTP). 2) Awareness of family planning services in the vicinity. 3) Decision making regarding contraceptive use. Methods: The study is a community based cross sectional observational study. The study was conducted among married women in reproductive age group. 342 married women were interviewed in the local language using a pre-tested questionnaire. Data was analyzed using SPSS version 17. Results: 87.7% of women were aware of at least one method of contraception. 68.4% women were using a contraceptive at the time of study. 14% women were unaware of any health care facility providing contraceptives in the vicinity. Knowledge and practice of Emergency Contraceptive was very low. Conclusions: Although there is high level of awareness, contraceptive use is not very high. New methods of motivating people to adopt and sustain Family Planning methods should be considered.